Analisis Rasio Keuangan Terhadap Profitabilitas Perbankan Syariah Indonesia - Dwi Yana Rahmalita; Pani Akhiruddin Siregar; Kadri Bancin (Jurnal Penelitian Medan Agama, 2019)
This research aims to analyses deeply the influence of CAR variable, NPF variable, FDR variable and BOPO variable to profitability. The profitability indicator is ROA variable. Quantitative data types in the form of monthly time-series data From The Financial Ratio Report of Sharia Commercial Bank and Sharia Business Unit published by Sharia Banking Directorate, Bank Indonesia and the Bank Licensing and Banking Information Department, Indonesia Financial Services Authority through Sharia Banking Statistics Bank Indonesia/Indonesia Financial Services Authority from January 2006 to December 2018. The results showed: (1) A regression model on the independent variable simultaneously affects the dependent variable, so that the independent variable regression model can be used to predict the dependent variable; and (2) The CAR variable and the FDR variable influential positive and significant toward ROA variable; NPF variable influential negative and significant toward ROA variable; BOPO variable influential negative and insignificant toward ROA variable.